Synchronous neuroendocrine tumor and signet ring cell carcinoma in the stomach: a case report and review of literature - Han, Jian; Wang, Ying; Mu, Hanlin; Liu, Jingmei (Frontiers in Medicine, 2025)
Synchronous neoplasms of the stomach are uncommon. Here we presented an unusual case with coexistence of neuroendocrine tumor and signet ring cell carcinoma in the stomach. Gastroscopic examination of a 66-year-old male patient showed a submucosal tumor-like mass with an ulcer on the surface located in the anterior wall of the lower segment of gastric body, confirmed by subsequent biopsy as a signet ring cell carcinoma. Moreover, we also found a slightly yellowish 6-mm protrusion simulating a polyp located in the lesser curvature of the upper segment of gastric body, and biopsy revealed it was a neuroendocrine tumor. The patient underwent a total gastrectomy with a standard D2 lymph node dissection. Pathohistological results led to the final diagnosis of synchronous neoplasms in the stomach, including a signet ring cell carcinoma and a neuroendocrine tumor.